Bottle with a message: The role of story writing as an engagement tool to explore children's perceptions of marine plastic litter. (January 2023) - Praet, Estelle; Baeza-Álvarez, Jostein; De Veer, Diamela; Holtmann-Ahumada, Geraldine; Jones, Jen S.; Langford, Sarah; Dearte, Jessica Michel; Schofield, John; Thiel, Martin; Wyles, Kayleigh J.
Abstract: As human behaviors play a crucial role in addressing the global threat of plastic pollution, it is vital to understand perceptions about marine plastic litter (MPL) and to develop interventions encouraging pro-environmental behaviors (PEBs). This study evaluates story writing as a window to explore perceptions and as an engagement activity to boost PEBs. During the COVID-19 lockdowns, schoolchildren from the East Pacific coast participated in this activity, each creating a story and answering a pre-post survey. Qualitative and quantitative analysis of 81 stories and 79 surveys show awareness of sources and impacts. Participants identified land and local pollution as significant contributors to MPL and emphasized bio-ecological impacts, reflecting concern for landscape and wildlife. While the stories presented a diversity of solutions, recycling dominated the surveys. As participants reported an increase in self-assessed knowledge and improved PEBs after this activity, it can be seen as an engagement tool to encourage behavior change. Highlights: A story-writing activity explored schoolchildren's perceptions of marine plastic litter. A pre-post survey examined impacts of the activity on the schoolchildren's perceptions and behaviors. Stories align with the regional context for sources and impacts of marine plastic litter. Solutions focus on recycling (in the surveys) and inadequate litter disposal (in the stories). Participation led to increased knowledge and enhanced the willingness to engage in pro-environmental behaviors.